Aislamiento, caracterización y actividad biológica de metabolitos secundarios de la especie Roupala montana de la provincia de Loja - Medina Aguinsaca, Juan Carlos (2018)
Abstract:In the present research work, secondary metabolites were isolated and characterized from the leaves of the Roupala montana species, using spectroscopic techniques such as nuclear magnetic resonance and gas chromatography coupled to mass spectrometry. Three compounds known as Kaur-16-ene, linolenic acid and alpha tocopherol from the Hexane extract were identified. The antimicrobial activity was evaluated by means of micro dilution in broth. The exact Hexane, Ethyl Acetate and Methanol were inactive for each of the bacterial strains. In addition, the essential oil of the dried plant was obtained by steam distillation. Through gas chromatography coupled to mass spectrometry and gas chromatography coupled to FID. 15 compounds were identified, with the majority being kaur-16-ene (77.2%), Kaur-15-ene (4.1%), phytol (3.45%), Nerolidol <(E) -> (2.22%), and Farnesyl acetone <(5E, 9E) -> (1.2%)